Education for superfluous population? The advent of artificial intelligence and the best students: a mindful pedagogy - Caligiuri, Mario (Formazione & insegnamento, 2018)
The advent of artificial intelligence hit both intellectual and manual labours. It will cause their disappearance or profound change. Consequently, today’s educational systems are largely training younger generation to careers without a future. This obvious issue has not been examined from a pedagogical point of view. Indeed, today’s governing elite may have no interest to worry about children of poor families’ education even though they were necessary for the army and the factories in the past. Thus, people risk to become superfluous, with a sharply division. On the one hand, there will be few people who are responsible to manage artificial intelligence’s development with a high-quality education. On the other, there will be multitudes with an education for leisure. Is an already determined destiny or there is anything you can do? May the answer to artificial intelligence be the enhancement of gifted people? May it be the strengthening of citizens’ education to avoid vast majority of people’s regression? Nevertheless, public education system should be reinvented as soon as possible. This essay pay attention on these urgent questions. We should answer thanks to education, the essential resource to keep the human being at the core of the universe.